Long-Term Neurocognitive and Psychosocial Outcomes After Acute Myeloid Leukemia: A Childhood Cancer Survivor Study Report. (14th August 2020) - Stefanski, Kristen J; Anixt, Julia S; Goodman, Pamela; Bowers, Katherine; Leisenring, Wendy; Scott Baker, K; Burns, Karen; Howell, Rebecca; Davies, Stella; Robison, Leslie L; Armstrong, Gregory T; Krull, Kevin R; et al.
Abstract: Background: Survivors of childhood acute myeloid leukemia (AML) are vulnerable to medical late effects of treatment; however, less is known about their psychosocial outcomes. This study evaluated neurocognitive and psychosocial outcomes in long-term AML survivors treated with bone marrow transplantation (BMT) or intensive chemotherapy (IC) without BMT. Methods: AML survivors (N = 482; median age at diagnosis = 8 [range = 0-20] years; median age at evaluation = 30 [range = 18-49] years) treated with BMT (n = 183) or IC (n = 299) and sibling controls (N = 3190; median age at evaluation = 32 [range = 18-58] years) from the Childhood Cancer Survivor Study were compared on emotional distress (Brief Symptom Inventory-18), neurocognitive problems (Childhood Cancer Survivor Study Neurocognitive Questionnaire), health-related quality of life (SF-36), and social attainment. Outcomes were dichotomized (impaired vs nonimpaired) using established criteria, and relative risks (RRs) were estimated with multivariable Poisson regression, adjusted for age at evaluation and sex. Results: AML survivors were more likely than siblings to report impairment in overall emotional (RR = 2.19, 95% confidence interval [CI] = 1.51 to 3.18), neurocognitive (RR = 2.03, 95% CI = 1.47 to 2.79), and physical quality of life (RR = 2.71, 95% CI = 1.61 to 4.56) outcomes. Survivors were at increased risk for lower education (RR = 1.15, 95% CI = 1.03 to 1.30), unemployment (RR = 1.41, 95% CI = 1.16 to 1.71), lower income (RR = 1.39, 95% CI = 1.17 to 1.65), and not being married or having a partner (RR = 1.33, 95% CI = 1.17 to 1.51). BMT-treated survivors did not differ statistically significantly from IC-treated on any outcome measure. Conclusions: AML survivors are at increased risk for psychosocial impairment compared with siblings; however, BMT does not confer additional risk for psychosocial late effects compared with treatment without BMT.